SOCIAL JUSTICE IN LAW, SOCIETY AND DEVELOPMENT: A MARXISM PERSPECTIVE OF INDONESIAN CASE - Arifin, Ridwan; Yuniar, Vania Shafira (UI Scholars Hub, 2021)
This article explores about social justice in peoples lives according to Karl Marxs prespective of the concept of social class. It also discusses Marxs concept of the struggle of the social class to provide a solution for the proletariat, to free themselves from the chain of cruelty, violence and alienation in the capitalist system to achieve social justice. The essence of social justice in Karl Marxs prespective is that if a society has created a manifestation of self through compassion, and the collaboration of a classless society, without violence, and without oppression, and humans are free from all forms of human alienation. Our main analysis is to examine the relationship between the concept of social class struggle and the need for a social revolution as a tangible form of justice for the formation of classless societies and also analyze the inhumane living conditions of the proletariat class in modern society. Marx considers freedom as a possibility for all people to develop their human potential, so that this thinking is the background of their social justice theory. This shows that social justice in Indonesia is a very important thing in the life of society and state for the sake of prosperity, peace and security.